Pengembangan Learning Manajemen System berbasis Aplikasi Teams dalam Menunjang Pembelajaran Jarak Jauh di SMA Negeri 1 Lasem - Imron Imron; Sulhadi Sulhadi (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
The Covid-19 pandemic since the beginning of the 2020/2021 academic year has made researchers consistently maximise the Microsoft Teams application as a Learning Management System (LMS) platform. LMS, better known as the concept of e-learning, is an effort to utilise information technology to accelerate the achievement of students' competence in a subject. LMS known as the concept of e-learning is an effort to utilise information technology in accelerating the achievement of learner competencies in a subject. Development of LMS based on Teams application in supporting PJJ. Teams-based LMS development in supporting PJJ at SMAN 1 Lasem is very useful. Both from schools, teachers, students and parents. As much as 82.71%.